Low‐Profile Planar Antenna Sensor Based on Ti3C2Tx MXene Membrane for VOC and Humidity Monitoring. Issue 13 (8th March 2022) - Khorsand Kazemi, Kasra; Hu, Shujun; Niksan, Omid; Adhikari, Kishor Kumar; Tanguy, Nicolas Roland; Li, Shibo; Arjmand, Mohammad; Zarifi, Mohammad H.
Abstract: Detection of volatile organic compounds (VOC)s is of great interest in industrial and environmental applications due to the severe impact of VOCs on human health and the environment, including climate change and ozone layer depletion. This study investigates the implementation of a Ti3 C2 T x MXene as radiating and sensing element to develop a VOC and humidity sensing antenna. The performance of the sensor is validated by introducing various VOCs, including acetone, ethanol, IPA, and methanol, in an isolated custom‐made chamber while the antenna sensor is communicating with a distanced receiver antenna. Measured results confirm that the exposure of the MXene antenna sensor to VOCs causes an upshift in the operating frequency of the antenna sensor. The study successfully demonstrates the potential of the proposed Ti3 C2 T x MXene antenna sensor in detecting acetone concentrations ranging from 8 to 80 parts per thousand (ppt). In addition, the sensor detects different humidity concentrations ranging between 77.8 ± 2% to 94 ± 1%, where for 94 ± 1% of humidity, a 213.1 MHz of frequency shift is observed. As a proof of concept, the developed MXene antenna sensor shows a promising potential for wireless gas and humidity sensing applications in the environmental and industrial sectors. Abstract : This work investigates the implementation of a Ti3 C2 T x MXene membrane as dual‐function sensing and radiating element to realize an antenna sensor for volatile organic compounds (VOC) and humidity detection. The results indicate that acetone, ethanol, IPA, methanol, and humidity affect the MXene antenna's response. The MXene antenna sensor demonstrates a great potential for wireless monitoring of VOCs and humidity in environmental and industrial applications.